Combustion Characteristics of Physically Mixed 40 nm Aluminum/Copper Oxide Nanothermites Using Laser Ignition - Saceleanu, Florin; Idir, Mahmoud; Chaumeix, Nabiha; Wen, John Z. (Frontiers in Chemistry, 2018)
This paper reports on the ignition and flame propagation characteristics of aluminum/copper oxide (Al/CuO) nanothermite at different packing density, manufactured from 40 nm commercial Al and CuO nanopowders. A 3.5 W continuous wave laser was used to ignite the samples in argon at atmospheric pressure, and a high speed camera captured the flame propagation. The high speed images revealed that the fast laser heating creates significant material ablation, followed by heat transfer along the heated surface. The bulk ignition occurs near the edge of the top surface, followed by the self-sustained burning. Lightly pressed powders (90% porosity) ignited in ~0.1 ms and the burning front propagated at around 200 m/s, while the dense pellets (40–60% porosity) ignited in ~1 ms and the burning front propagated at around 10 m/s. These results indicate that the reaction mechanism changes from mass convection to heat diffusion with increasing the packing density. The ignition and burn speeds of these Al/CuO nanothermites at different equivalence ratios (ERs), along with SEM images of pre- and post-combustion, illustrate that the homogeneity of the mixture is a critical parameter for optimizing the performance. The Al rich mixtures show significantly lower ignition delays and higher burn speeds.